Qualitative and Molecular Screening of Potential Ligninolytic Microbes from Termite (Coptotermes curvignathus) Gut - FREDDIE SIMOL, CARLINA; CHUBO, JOHN KEEN; KING, PATRICIA JIE HUNG; ONG, KIAN HUAT; CHEW, CINDY; NAWI, KHALID (Borneo Journal of Resource Science and Technology, 2021)
Ligninolytic microbes have great potential in converting high lignin by-products to more utilisable products by decomposing the lignin-rich agricultural and industrial wastes. Thus, the aim of this study are to screen and identify the potential ligninolytic microbes from the termite (Coptotermes curvignathus) gut. The study was conducted at Universiti Putra Malaysia Bintulu Sarawak Campus, Malaysia. Twenty-seven microbes isolated from termite gut obtained from the Microbiology Laboratory, Faculty of Agricultural Science and Forestry, were used for the ligninolytic activity screening. Media with four different ligninolytic indicator dyes (Azure B, phenol red, methylene blue, and Remazol Brilliant Blue) were streaked with microbial isolates and incubated at 37 °C for 48 h. Out of twenty-seven microbe isolates, only three (CH2, CH5, and CH9) isolates showed decolourisation zone indicating the positive presence of ligninolytic activity. The 16S rRNA gene sequence data indicated the isolates are highly homologous to Bacillus spp.